Plany rozwoju infrastruktury i działalności turystycznej w parkach krajobrazowych na terenie administrowanym przez Lasy Państwowe - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2015)
The aim of the study was to present plans (up to 2030) for the development of infrastructure and tourism activities in the Polish landscape parks located in the area of the State Forests’ administration. At the end of 2013, a survey was conducted the results of which were verified and their analysis completed in 2014. The questionnaire was sent to the directorates of all 122 parks. 70.5% of the directorates replied to the open question inquiring about their plans and demands for tourist activities (including educational tourism) and recreation. These were then correlated to parks in areas under the State Forests’ administration. The most commonly proposed/planned actions by the directorates in cooperation with the Forest Districts are: construction of new educational paths (in 41.9% of parks), maintaining the existing ones (24.4%) and the organization of tourism/recreation and educational events (22.1%). The largest share of proposed/planned actions without the cooperation of the Forest Districts comes from the creation of new routes/trails, parking lots, etc. along with their equipment (36.0%), construction of tourist infrastructure (bins, benches, tables, shelters, fire circles, sightseeing towers, bridges, 18.6%) and the issuing of maps, brochures, guides or other publications (17.4%). However, it is of particular importance to take the need for nature conservation in the development of tourism and recreation in areas of landscape parks into account. The literature provides a number of helpful solutions. Furthermore, such activity requires broad cooperation supported by external funds especially between the parks, Forest Districts and municipalities. It is also important to continue the environmental education of both, visitors and locals, as well as the promotion of eco-tourism and responsible use of the environment.